Opportunities of Antidiabetic Drugs in Cardiovascular Medicine: A Meta-Analysis and Perspectives for Trial Design. Issue 2 (August 2020) - Yan, Cen; Thijs, Lutgarde; Cao, Yu; Trenson, Sander; Zhang, Zhen-Yu; Janssens, Stefan; Staessen, Jan A.; Feng, Ying-Mei
Abstract : To identify potential application of GLP1-RAs (glucagon-like peptide-1 receptor agonists) and SGLT2-Is (sodium-dependent glucose cotrasnsporter-2 inhibitors) in cardiovascular medicine, we performed PubMed search until March 31, 2020 and selected placebo-controlled randomized trials (RCTs) in patients with type 2 diabetes mellitus. Twenty-four hour ambulatory and office blood pressure (BP), major adverse cardiovascular events (MACE), progression of chronic kidney disease (CKD), and changes in glycated hemoglobin and body weight were aggregated across RCTs using random-effect models. In 2238 patients (7 RCTs), SGLT2-Is lowered 24-hour systolic/diastolic BP by 4.4/1.9 mm Hg (95% CI, 3.4–5.5/1.2–2.6 mm Hg), whereas 2 GLP1-RAs RCTs produced contradictory BP results. Over 1.3 to 5.4 years of follow-up of 56 004 patients (7 RCTs), aggregate hazard ratios associated with GLP1-RA treatment were 0.88 (0.84–0.93) for MACE, 0.84 (0.74–0.89) for CKD, and ranged from 0.84 to 0.90 for individual MACE end points ( P ⩽0.01). Across 5 SGLT2-Is RCTs, including 43 467 patients with 1.5 to 4.2 years follow-up, hazard ratios were 0.87 (0.82–0.93) for MACE, 0.68 (0.62–0.75) for HF, 0.82 (0.72–0.93) for cardiovascular death, 0.87 (0.79–0.96) for myocardial infarction, and 0.61 (0.56–0.67) for worsening CKD. The risk of HF and CKD, but not MACE, decreased with more BP lowering. Stricter glycemic control was associated with higher HF risk, but unrelated to MACE or CKD. The aggregate effect sizes on systolic BP, body weight, and glycated hemoglobin were −1.61 mm Hg, −2.40 kg, and −0.69% for GLP1-RAs, and −2.53 mm Hg, −1.15 kg and −0.24%, for SGLT2-Is ( P <0.001). In conclusion, GLP1-RAs and SGLT2-Is reduced cardiovascular risk with differential benefit profiles. Abstract : Supplemental Digital Content is available in the text.